DEVELOPMENT OF LEARNING TECHNIQUES OF BASIC TECHNIQUES BASED ON CURRICULUM 2013 BASED ON SPORTS AND HEALTH EDUCATION IN BASIC SCHOOL - Dulmanan Dulmanan; Iyakrus Iyakrus; Meirizal Usra (Sriwijaya University Learning and Education International Conference, 2018)
The purpose of this research is 1) to know the development of learning model of basic soccer technique based on curriculum 2013 on physical education of sport and health in elementary school. 2) To know the effectiveness of the development of the basic soccer learning model based on the 2013 curriculum on physical and health education in elementary school. This research uses research and development method (Research and Development). The sample in this research is as many as 54 students from 3 elementary school that is SD Negeri 120, SD Negeri 156 and SD Negeri 230. The result of research shows the learning of football technique more effective and efficient. Thus, it can be explained that the development of the basic soccer learning model based on the 2013 curriculum on physical and sports education in elementary school is more effective and efficient. This means that the better the development of the basic soccer learning model based on the 2013 curriculum implemented, the better the results obtained in physical education of sports and health in elementary schools for students.